An assessment of knowledge and practices of breastfeeding among mothers having child less than 2 years of age in a city of central Uttar Pradesh, India - Kumar, Bipul; Bose, Tathagata; Das, Saurav; Gupta, Ashish Kumar; Kumar, Ashutosh; Bhandari, Ashok (International Journal of Contemporary Pediatrics, 2020)
Background: Breastmilk is the natural first food for babies which provides all the energy and nutrients that the infant needs for the first few months of life. More than two thirds of the 2.4 million child deaths occurring each year in India are related to inappropriate infant feeding practices. Initiation of breastfeeding within 1 hour of birth in central Indian states is among the lowest. The situation in central Indian states especially Uttar Pradesh is worse than the rest of India which is usually attributed to prevalent socio-economic and cultural factors. Methods: A cross-sectional descriptive study that was conducted among 144 mothers visiting a tertiary care hospital in Lucknow, Uttar Pradesh, India over a period of nine months using a questionnaire-based interview. Results: The study found that majority of subjects has good knowledge about breastfeeding. 92.4% mothers reported knowledge of putting the baby on the breast within an hour of birth. 65% had the correct breastfeeding position knowledge. Majority were aware that breastfeeding protects from various infections and that colostrum or first milk serves as the first immunization for the baby. 90.3% knew the correct definition of complementary feeding. Most of the subjects planned to breastfeed their baby for a year or more (86.8%). Conclusions: Majority mothers had good knowledge of breastfeeding and complementary feeding and good breastfeeding practices were being followed. This study brought out that educated mothers had better breastfeeding knowledge and practices, thus highlighting to the importance of formal education in mothers.